The provision of facilities and services for the neighbourhood a case study of neighbourhood areas in Manjung Perak / Norainah Abdul Rahman - Abdul Rahman, Norainah (2017)
Neighbourhood is a place where the community is attached with the land use and amenities. The facilities and services are important aspect to the residents in their neighbourhood. The neighbourhood facilities and services are based on the planning guidelines were adopted by local governments. The issue that is often being questioned is the provision that can meet the residents’ requirements and needs. The aim of this study is to establish facilities and services evaluation approach. The study has developed a satisfaction model incorporated with physical and social factors to establish the evaluation approach. Empirical research has shown the importance of residents’ evaluating their neighbourhood. The physical factors are adequacy, amenity condition, distance, accessibility and maintenance. The social factors are feeling convenient, feeling safe and feeling comfort. The research design employed the quantitative approach with qualitative data. The quantitative approach was used to collect primary data from the residents through a questionnaire survey. The qualitative data was used to collect both primary and secondary data. The primary data is from the open-ended questions in the questionnaire survey and the site inventory survey. The secondary data is from the local government and agencies related. Three selected neighbourhoods in Manjung Perak Malaysia are in Seri Manjung, Sitiawan and Lumut. The evaluation was to measure the level of satisfaction among the residents on the existing facilities and services in their neighbourhood. The guidelines used by the local government were also appraised to compare the compliance of facilities and services provided with the planning guidelines. There are three key findings of the research. The first shows that all level of satisfaction of different socio demographic (M=3.33) and socio economic (M=3.55) are at the moderate level. The second key finding demonstrates the physical factors all satisfaction at moderate level but by rank it show that the highest to the lowest rank are accessibility (M=3.54), adequacy (M=3.51), amenity condition (M=3.48), distance (M=3.48) and maintenance (M=3.46) of facilities and services. While for social factors, all satisfaction are at the moderate level but by rank are feeling convenient (M=3.61), feeling safe (M=3.60) and feeling comfort (M=3.60). Comparing with the guidelines the adequacy is not fulfilled, amenity condition and maintenance are at moderate condition, and distance and accessibility are fulfilled. The third key finding illustrates a weak correlation below R=0.510** both ways the physical factors with social factor (R=0.425) and the social factors with the physical factors (R=0.427). Even though it is a weak correlation but it can be ranked with strongest and weakest correlation. For physical factors with social factors is felling comfort, feeling convenient and feeling safe. For social factors with physical factors are maintenance (R=0.479), amenity condition (R=0.458), adequacy (R=0.453), distance (R=0.387) and accessibility (R=0.359). As a conclusion the residents’ satisfaction is very important in provision of neighbourhood facilities and services. The physical and social factors are significant to meet the residents’ needs and requirements. This will reflect the policy implication in terms of future neighbourhood developments.